Psychosocial aspects and mental health burden of pediatric MASLD - Vanishri Ganakumar; Abhinay Mahaling; Manjunath Goroshi; Vikrant Ghatnatti (Frontiers in Endocrinology, 2026)
Metabolic dysfunction–associated steatotic liver disease (MASLD) is the most common chronic liver disease of childhood and the hepatic component of a systemic metabolic and endocrine disorder linked to obesity and insulin resistance. Its psychological and social dimensions, however, remain under-recognized relative to its metabolic features. Affected children carry a substantial mental-health burden: elevated rates of depression, anxiety, disordered eating, and impaired quality of life that both reflect and aggravate the underlying disease. This mini review uses the biopsychosocial model to summarize current understanding of this burden in pediatric MASLD. We outline the bidirectional neuroendocrine and inflammatory mechanisms that link metabolic dysfunction with psychological distress, including cytokine signalling, leptin and adipokine dysregulation, hypothalamic–pituitary–adrenal axis activation, and the gut–brain axis. We then consider the social determinants and system-level barriers that shape outcomes, practical approaches to screening and integrated multidisciplinary management, and the psychosocial considerations raised by emerging pharmacotherapies such as glucagon-like peptide-1 receptor agonists. We highlight areas of ongoing debate: notably the tension between weight-centred intervention and the risk of precipitating disordered eating, and the neuropsychiatric monitoring of new pharmacological agents, together with the principal research gaps and likely future directions. Recognizing pediatric MASLD as a biopsychosocial condition, and embedding mental-health assessment within routine metabolic care, may improve both hepatic and psychological outcomes in this growing population.